2013
DOI: 10.1007/s00383-013-3426-1
|View full text |Cite
|
Sign up to set email alerts
|

Thromboses of the pampiniform plexi after subinguinal varicocelectomy

Abstract: Spermatic vein thrombosis after surgery is a rare complication but its onset should be considered as a possible event in patients with inguinal and scrotal pain. To manage this condition after diagnosis surgeons may opt for a surgical or clinical approach, either with drugs or local heat, rest and scrotal support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
0
5
0
4
Order By: Relevance
“…Thrombosed varicoceles have been described as a rare cause of acute scrotal pain [ 2 – 4 ]. Postoperative thrombus in pampiniform plexuses have been managed conservatively with intravenous antibiotics, parenteral and oral analgesics, scrotal elevation with bed rest [ 3 ]. Spontaneously occurring thrombi have also been reported to have been managed medically in a previous case, though the exact details of medical treatment are unclear [ 2 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thrombosed varicoceles have been described as a rare cause of acute scrotal pain [ 2 – 4 ]. Postoperative thrombus in pampiniform plexuses have been managed conservatively with intravenous antibiotics, parenteral and oral analgesics, scrotal elevation with bed rest [ 3 ]. Spontaneously occurring thrombi have also been reported to have been managed medically in a previous case, though the exact details of medical treatment are unclear [ 2 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of thrombosis of the pampiniform venous plexus after subinguinal varicocelectomy being already described [4], the etiology of spontaneous spermatic venous thrombosis remains unknown. Different hypotheses have been described including prolonged stress (or sexual activity) [5-7] or Buerger’s disease [5, 8].…”
Section: Discussionmentioning
confidence: 99%
“…7 Kayes et al reported that spontaneous vein thrombosis could be related to prolonged vigorous sexual activity or sport activity, tumours of the genitourinary tract, infections, trauma, inguinal hernia surgery, long-hour flights, and the use of some drugs. 8 Mirilas et al cautioned for a complex system that should be carefully considered when opting for the subinguinal approach and found it necessary to carry out a comprehensive preoperative hemodynamic assessment of the vein reflux to decide on the most suitable surgical technique.…”
Section: Discussionmentioning
confidence: 99%